Model Komunikasi Dakwah Dai Lembaga Pemasyarakatan Kelas II-A Pekalongan - Mukhammad Adib Fahmi; Teddy Dyatmika (Universitas Islam Balitar, 2022)
Prisoners are identical to someone who has committed a crime and is difficult to be accepted again in society. Prisoners are also identical with someone who it difficult to receive messages of kindness, especially messages from preachers. This is different from the Class II-A Penitentiary in Pekalongan, which is very enthusiastic about participating in da'wah activities. The communication model carried out can be well received by prisoners. The purpose of this study is to analyze the communication model used in conducting da'wah to prisoners. This study uses a qualitative research method using purposive sampling, namely preachers, correctional officers, and prisoners. The method of data collection was carried out by in-depth interviews. The results showed that the communication model that was carried out was very good so that it was able to make inmates enthusiastic in participating in these activities. The inhibiting factors in da'wah activities include the busyness of the preacher which makes da'wah cannot be done frequently, the second is environmental factors in prisons that are often exposed to rob, and the third factor is that communication technology has not been optimized to carry out da'wah in correctional institutions.